(untitled) (Conversatoria Linguistica, 2020)
This article presents a group of slogans advertising cit-ies within Mazowieckie District. In the description of slogans I focus primarily on their construction, stylistic character and key words contained in them. I pay attention to what is typical of territorial brands and what differs from the convention. The main aim of my interpretation is to show that the slogan does meet its purpose – builds a positive image of the advertised brand, and thus the whole Mazowieckie District.